From social to socio-material pathologies: on Latour, subjectivity and materiality. Issue 2 (3rd May 2016) - Hoffmann Birk, Rasmus
ABSTRACT: This article produces an encounter between the concept of 'social pathology' and the work of the philosopher Bruno Latour. It offers an introduction to Latour's style of thought with regard to subjectivity. It argues that subjectivity is not an interiorized property of people, but a processual accomplishment from associating with different actors, which may be human or non-human. Subjectivity, from this point of view, exists in the interstice between affecting the world and being affected. Building on this Latourian perspective, the article goes on to argue that social pathologies should not be seen as a function of 'society', but rather as socio-material patterns of activity that spread across different spaces and places. Thus, the article posits that a more apt term for 'social pathologies' would be 'socio-material pathologies'. It finishes by discussing the implications of these perspectives for both critique and methodology in social research.